Cost of Production for Processed Oranges in Southwest Florida in 2019/20 - Ariel Singerman (EDIS)
This article presents a summary of the 2019/20 costs of production for processed oranges grown in southwest Florida. The methodology chosen to collect the data consisted of surveying growers directly so as to reflect their costs. The main changes this season were the decrease in fertilizer and nutritionals spending, and the increase in insecticides. The total cost of production for processed oranges in 2019/20 was $2,095.05 per acre.